ANALISA KESESUAIAN MASUKAN HEAT INPUT PADA PENGELASAN GTAW UNTUK MATERIAL SOLID INCONEL UNS N06625 - Hilmy, Zakwan; Susilo, Trisno; Tyas Adi, Fajar; Milang Aran, Mikhael (Fakultas Sains dan Teknologi Universitas Karimun, 2024)
Currently metal joining (welding) is widely needed in the world of fabrication, mining and shipping construction. Good welding has a guiding procedure in the form of WPS. WPS has several parameters that determine heat input. This research was conducted to determine the compatibility between the parameters in the procedures used and the actual parameters used in the field. The research was carried out on 3 samples that had the same dimensions, namely a diameter of 4